KUALITAS PELAYANAN TERHADAP MINAT PASIEN DALAM MEMANFAATKAN KEMBALI JASA PELAYANAN RAWAT JALAN RUMAH SAKIT DI MASA PANDEMI COVID 19: LITERATURE REVIEW - Gugun Gunawan Ahmad; Budiman Budiman; Setiawati Setiawati; Yayat Suryati; Iin Inayah; Andria Pragholapati (Universitas Muhammadiyah Kudus, 2022)
The COVID 19 pandemic currently occurring has affected hospital operations and occupancy rates. The COVID-19 pandemic affects dimensions in the quality of services provided in hospitals. Researchers are interested in conducting literature research with the title: